2004
DOI: 10.1080/1478641032000101714
|View full text |Cite
|
Sign up to set email alerts
|

Butenolides from a cultured microfungus, Acremonium sp

Abstract: Two related butenolides have been isolated from a culture broth of a strain of the fungus, Acremonium sp. Although the lactone acid (3) is a known compound, the structure of the lactone diacid (4), deduced by spectroscopic analysis, is assigned for the first time. This compound appears to be identical to a partly characterised metabolite isolated, along with 3, from Chaetomium indicum in 1953.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Compounds 7 and 8 are related butenolides, reported to be produced by several ascomycetes, including Talaromyces rugulosus (Küppers et al, 2017), Acremonium sp. (Ghisalberti et al, 2004) and even already known from another Cytospora sp (Lu et al, 2011). Due to the structural similarity between the two heptanedioic acid derivatives 1 and 2 and these butanolides, we proposed a plausible biogenetic pathways for the formation of the new metabolites.…”
Section: Structure Elucidationmentioning
confidence: 70%
“…Compounds 7 and 8 are related butenolides, reported to be produced by several ascomycetes, including Talaromyces rugulosus (Küppers et al, 2017), Acremonium sp. (Ghisalberti et al, 2004) and even already known from another Cytospora sp (Lu et al, 2011). Due to the structural similarity between the two heptanedioic acid derivatives 1 and 2 and these butanolides, we proposed a plausible biogenetic pathways for the formation of the new metabolites.…”
Section: Structure Elucidationmentioning
confidence: 70%
“…2(5H)-Furanone (alternatively also known as c-crotonolactone or D ab -butenolide) is a simplest sub-unit of a large class of fivemembered heterocyclic a-carbonyl compounds. The furanone sub-unit is present in a large number of natural products [1][2][3][4][5][6], which display a wide range of biological activities, and is present in a number of drugs with diverse biological activities, such as antifungal, antibacterial and anti-inflammatory. Recently, it has been shown that 2(5H)-furanone plays an important role in cheese technology [7].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the biological and pharmaceutical importance, 2(5H)furanone (from here onwards: furanone) and 2(5H)-thiophenone (from here onwards: thiophenone) attract considerable attention as synthetic targets and intermediates [10][11][12][13][14]. Furanone and thiophenone possess an sp 3 carbon atom (at position 5, see Scheme 1) that, in the presence of unequal substituents (at positions 9 and 10), affords chirality. Then, furanone and thiophenone are used in stereoselective synthesis [15,16] to produce chiral compounds and to determine the influences and relative configurations of stereogenic centres [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…(i) For 2-(5H)-furanone, the system used for the calorimetric measurements was a static bomb calorimeter, equipped with a twin valve bomb (type 1105, Parr Instrument Company), made of stainless steel and with an internal volume of 0.340 dm 3 . The apparatus and technique have been previously described [27,28].…”
Section: Combustion Calorimetrymentioning
confidence: 99%
“…The 2-(5H)-furanones, also known as crotonolactones or butenolides, are naturally occurring compounds which are associated with a variety of biological phenomena [1][2][3][4]. They have been isolated from Streptomyces species [5][6][7], from Hortonia species [8] and are also produced by marine green, red or brown algae, by sponges, fungi, and ascidians [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%